ANALISIS FAKTOR-FAKTOR PENGHAMBAT PELAKSANAAN PEMBELAJARAN DARING SELAMA MASA PANDEMI COVID-19 OLEH GURU IPA SMP SE-KOTA JAYAPURA - Megawati, Ruth; Rophi, Apriani Herni (Jurnal Ilmiah Mandala Education (JIME), 2022)
The Covid-19 pandemic has caused the education process to shift from a face-to-face learning system to bold learning. Drastic changes in the learning system caused a lack of readiness in planning and in its implementation which resulted in ineffective learning poses. Teachers as one of the main factors determining the success of learning also experience obstacles in carrying out learning boldly. This study aims to inhibiting factors faced by junior high school teachers in Jayapaura City in carrying out bold lessons during the Covid-19 pandemic. This study is a quantitative study with a population of all junior high school teachers in the city of Jayapura which collected 89 people, while the sample in this study was teachers who carried out bold learning where the sample was taken purposively. Data analysis was carried out on each indicator of the variables studied, by presenting each score from the indicator which would then be confirmed in the table of score interpretation criteria achieved. Based on the research, the results obtained are factors that inhibit the implementation of learning from science teachers in junior high schools in Jayapura City, namely the availability of bold learning facilities in the less good category (2.51) and student interest in learning in the poor category (2.36).